(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
Fear seems to be an integral part of the religious praxis connected to anuttara-yoga tantras. Fear induced in ritual contexts significantly facilitated achieving results considered to be soteriologically essential. That emotion was regarded to be useful temporarily and eliminated at an advanced stage of the praxis. Fear was induced mainly by monstrous images of aggressive gods and by transgressive rituals. It seems that anxiety was performing following functions in early Vajrayāna: it caused psychic mobilization and enhanced personal involvement of ritual participants, it acted as a motivator of religiosity, it increased faith in the corresponding cosmology and soteriology, it enabled memories encoding typical for imagistic mode of religiosity (invoking the theory of H. Whithouse), it brought on followers’ identity crisis needed for final transformation, it contributed to occurring of mystical experiences, it made trust in guru stronger, it reduced emotional reaction to stressful stimuli after some time.